Gender Dan Karakteristik Coping Trauma Pada Anak Pasca Bencana - I Gusti Ayu Agung Noviekayati; Isrida Yul Arifiana; Anrilia Ema Mustikawati Ningdyah; Salindri Anita Rahman; Aninditha Azzahra (Universitas Nahdlatul Ulama Blitar, 2026)
Natural disasters are traumatic events that can have significant psychological effects on children, who are emotionally vulnerable and rely on various coping strategies to manage trauma. This study examines the characteristics of trauma coping strategies used by children following a disaster and explores gender differences in the selection of these strategies. Five coping domains are analyzed: problem-focused coping, positive cognitive restructuring, support-seeking strategies, distraction strategies, and avoidance strategies. A quantitative survey approach with accidental sampling was employed. The participants were 889 children aged 10-12 years from 21 elementary schools in the Ponorogo area who were affected by a disaster. Data were analyzed using descriptive statistics through SPSS software. The findings reveal that positive cognitive restructuring is the most frequently used coping strategy among children after disasters. Gender differences were also identified, with girls use positive cognitive restructuring more often, while boys are more likely to employ distraction strategies to cope with psychological stress. These results highlight the importance of considering gender based coping patterns in post disaster psychological interventions. The study provides valuable insights for school and government agencies in developing effective coping strategy programs, particularly by strengthening positive cognitive restructuring skills to support children’s psychological recovery after disaster.